Transcranial Motor-Evoked Potentials Are More Readily Acquired Than Somatosensory-Evoked Potentials in Children Younger Than 6 Years. Issue 6 (December 2016) - McIntyre, Ian W.; Francis, Lisa; McAuliffe, John J.
Abstract : (Abstracted from Anesth Analg, 122:212–218, 2016) Researchers attempted to prove or disprove the theory that somatosensory-evoked potentials (SEEPs) are easier to obtain than transcranial motor-evoked potentials (TcMEPs) in children younger than 6 years. The study also sought to test the assumption that motor-evoked potentials are rarely obtained in children younger than 2 years.